Association Between Intimate Partner Violence and Depressive Symptoms among Women Aged 15 to 45 Years in Peru: A Three-Year Analysis of the Demographic and Health Survey - Silva-Burga, Alejandro (2022)
We conducted a secondary data analysis based on the 2014, 2015, and 2016 Demographic and Health Surveys to determine the association between intimate partner violence (IPV) and depressive symptoms in Peruvian women aged 15–45 years. Depressive symptoms were assessed through the PHQ-9, while IPV was assessed through the CTS-2. A total of 24,099 subjects were included. The prevalence of depressive symptoms and IPV was 6.98% and 64.72%, respectively. Victims of IPV were 2.47 times more likely to have depressive symptoms compared to those who were never assaulted. In conclusion, there is a strong association between IPV and depressive symptoms.